Intestinal Parasites and "Progress": A case study from Urabá, Antioqueño (Colombia) (2017)
ABSTRACT: Background: Infections with intestinal parasites in humans can be understood using the model of disease and illness as an ongoing process. The presence, persistence, and dissemination of intestinal parasites are determined by the living conditions prevalent in societies and by differences related to social class. There is a paucity of both international and national studies examining the relationship between living conditions and the prevalence of human parasites in Colombia. There are even fewer studies that adopt a historical approach to this relationship. Research Question: a) to compare current data on the prevalence of intestinal parasites in the region of Urabá (a subregion of the Colombian province of Antiqueño) with data collected 50 to 75 years ago; b) to explore the relationship between prevalence of intestinal parasites and living conditions during these time periods. Methodology: A literature review was performed to characterize living conditions and prevalence of intestinal parasites during the two periods of interest (contemporary statistics and those from 50-75 years ago). Results: Both study periods were characterized by a high prevalence of intestinal parasites and substandard living conditions Conclusions: With respect to human parasites and living conditions, little has changed in Urabá in the last 50 years. Economic progress has benefited only a few. Social "progress" has yet to touch the vast majority of people in Urabá.